The Potential Prognostic Role of Oligosaccharide-Binding Fold-Containing Protein 2A (OBFC2A) in Triple-Negative Breast Cancer - Wu, Qianxue; Tang, Xin; Zhu, Wenming; Li, Qing; Zhang, Xiang; Li, Hongyuan (Frontiers in Oncology, 2021)
Background Patients with triple-negative breast cancer (TNBC) have poor overall survival. The present study aimed to investigate the potential prognostics of TNBC by analyzing breast cancer proteomic and transcriptomic datasets. Methods Candidate proteins selected from CPTAC (the National Cancer Institute’s Clinical Proteomic Tumor Analysis Consortium) were validated using datasets from METABRIC (Molecular Taxonomy of Breast Cancer International Consortium). Kaplan-Meier analysis and ROC (receiver operating characteristic) curve analysis were performed to explore the prognosis of candidate genes. GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) enrichment analysis were performed on the suspected candidate genes. Single-cell RNA-seq (scRNA-seq) data from GSE118389 were used to analyze the cell clusters in which OBFC2A (Oligosaccharide-Binding Fold-Containing Protein 2A) was mainly distributed. TIMER (Tumor Immune Estimation Resource) was used to verify the correlation between OBFC2A expression and immune infiltration. Clone formation assays and wound healing assays were used to detect the role of OBFC2A expression on the proliferation, invasion, and migration of breast cancer cells. Flow cytometry was used to analyze the effects of silencing OBFC2A on breast cancer cell cycle and apoptosis. Results Six candidate proteins were found to be differentially expressed in non-TNBC and TNBC groups from CPTAC. However, only OBFC2A was identified as an independently poor prognostic gene marker in METABRIC (HR=3.658, 1.881-7.114). And OBFC2A was associated with immune functions in breast cancer. Biological functional experiments showed that OBFC2A might promote the proliferation and migration of breast cancer cells. The inhibition of OBFC2A expression blocked the cell cycle in G1 phase and inhibited the transformation from G1 phase to S phase. Finally, downregulation of OBFC2A also increased the total apoptosis rate of cells. Conclusion On this basis, OBFC2A may be a potential prognostic biomarker for TNBC.